2008
DOI: 10.1016/j.biopsych.2008.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Visual Perception and Its Impairment in Schizophrenia

Abstract: Much work in the cognitive neuroscience of schizophrenia has focused on attention, memory, and executive functioning. To date, less work has focused on perceptual processing. However, perceptual functions are frequently disrupted in schizophrenia, and thus this domain has been included in the CNTRICS (Cognitive Neuroscience Treatment Research to Improve Cognition in Schizophrenia) project. In this article, we describe the basic science presentation and the breakout group discussion on the topic of perception f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
363
3
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 417 publications
(399 citation statements)
references
References 86 publications
28
363
3
5
Order By: Relevance
“…The current data are consistent with empirical findings and formulations in the literature that have highlighted aberrant neural responses in visual cortices that could underlie deficits in sensory registration and/or propagation of feedforward-mediated information in ScZ (Tan et al, 2013;Javitt, 2015, Butler et al, 2008. In the visual cortex of ScZ patients, reduced synaptic contacts (Selemon et al, 1995) as well as reduced markers of interneuron activity have been observed (Hashimoto et al, 2008), which together could provide possible mechanisms for the observed reductions in high-frequency oscillations as these are critically dependent upon rhythmic inhibition of large number of pyramidal cells (Whittington and Traub, 2003).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The current data are consistent with empirical findings and formulations in the literature that have highlighted aberrant neural responses in visual cortices that could underlie deficits in sensory registration and/or propagation of feedforward-mediated information in ScZ (Tan et al, 2013;Javitt, 2015, Butler et al, 2008. In the visual cortex of ScZ patients, reduced synaptic contacts (Selemon et al, 1995) as well as reduced markers of interneuron activity have been observed (Hashimoto et al, 2008), which together could provide possible mechanisms for the observed reductions in high-frequency oscillations as these are critically dependent upon rhythmic inhibition of large number of pyramidal cells (Whittington and Traub, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, as gamma-band activity was also unimpaired in early visual cortex, the most parsimonious interpretation of the MEG data would favour a deficit in ventral stream generators. This conclusion is consistent with recent data that highlight that reductions in P1 amplitude may mostly involve impaired contributions from extra-striate cortex while initial afferent activity (through magnocellular pathways) to early visual cortex is intact in ScZ patients (Lalor et al, 2012; for different findings, however, see e.g., Butler et al, 2008;Javitt et al, 2009Javitt et al, , 2015.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This finding is not directly relevant to the main question addressed in this study but it is interesting because it contrasts with previous studies in patients with established schizophrenia who show reduced ability to spontaneously disambiguate two-tone images of faces without prior knowledge (46,47). This previous effect is most likely related to well-established schizophrenic deficits in early and midlevel vision that affect perceptual organization, context processing and integration (37,38,(48)(49)(50)(51)(52)(53) rather than to top-down influences from high-level visual cognition as in the current study. We did not directly probe early and midlevel visual function in our participants, but it seems most likely that the absence of impairments in spontaneous disambiguation of two-tone images in the clinical group might be due to the specific nature of our stimulus material, which was extensively piloted to be difficult to disambiguate without prior knowledge (for details, see SI Materials and Methods).…”
Section: Discussioncontrasting
confidence: 88%
“…Indeed, the importance of multisensory integration was recognized by the first CNTRICS (Cognitive Neuroscience Treatment Research to Improve Cognition in Schizophrenia) breakout session, which suggested the inclusion of 'cross-modal integration' in a preclinical battery for cognition in schizophrenia research (Butler et al, 2008). We have recently introduced a cross-modal (tactile-to-visual) variant of the rodent spontaneous object recognition (SOR) task that enables assessment of multisensory integration (Winters and Reid, 2010).…”
Section: Introductionmentioning
confidence: 99%